Clinical Communication (Handover) and Safety of Nursing Care: a literature review - Brás, Cláudia (2016)
Introduction: The handover as a process of transference of responsibilities is considered a crucial moment in the provision of nursing quality care. Problems in communication are the major causes of errors that occur during situations of handover. Objectives: We propose to identify the evidence of the relationship of clinical communication (handover) and safety of nursing care. Methods: We accomplished an integrative literature review using Pubmed, Web of Science, Scopus, CINAHL data bases. A research across the terms: “Patient Handoff”, “Patient Safety”, “Clinical Communication”, “Nursing” was realized. In studies for research strategy emerged 137 articles. We selected 8 articles that responded to the purpose of this study. As inclusion criteria, studies published between January 2010 and March 2016 were established, available in Portuguese and English. Results: The analysis of the articles through critical identified convergences allowing the following grouping by themes: handoveras a process of the transference of responsibility, barriers to effective communication and strategies promoting a handover withquality. Conclusions: The quality of information during the handover allows nurses to organize interventions anticipating risks. It is essential to identify barriers that interfere with the handover process, for being able to implement strategies that constitute an effective communication process and promote the safety of the patient.